Arogyavardhini Vati – Critical Analysis of a Miracle Drug - Sahoo, Preetimayee; Mahanta, Nihar Ranjan; Mishra, Sanjay Kumar (International Research Journal of Ayurveda & Yoga, 2024)
Introduction: Arogyavardhini Vati is a herbomineral preparation which has miraculous effects on many diseases. It has the ability of balancing Tridosha and is beneficial in many liver disorders, dyslipidemia, metabolic syndrome, skin diseases, etc. Many clinical research and animal studies have been done to establish its actions in various diseases and its safety during use. Material and Methods: Here, in this article, an attempt is made to collect all the literary data about Arogyavardhini Vati from our treaties and all the research articles available. These data are compiled and analyzed and the results obtained are presented. Results: The Rasapanchaka analysis shows that Arogyavardhini Vati is Tikta Rasa Pradhana (27.59%) followed by Kashaya (24.14%) and Katu (20.69%) rasa, predominant in Laghu (29.03%) and Ruksha Guna (29.03%), Ushna Virya predominant (54.55%), and the Vipaka was katu (54.55%). Discussion: Research evidence shows that Arogyavardhini Vati is effective on various liver diseases such as hepatitis, non-alcoholic and alcoholic fatty liver, Jalodara or ascites due to liver disorder, and autoimmune liver disease. Animal experiments also proved its hepatoprotective activities. It has anti-hyperlipidemic action, helps in metabolic syndrome, and is beneficial in many skin diseases. It reduces the pus discharge in karna srava or chronic suppurative otitis media. Studies show that pharmaceutical and analytical parameters for Arogyavardhini Vati are validated by HPTLC method. Toxicity studies show no accumulation or toxic effect of mercury and copper on vital organs. Conclusion: Arogyavardhini vati is safe and miraculously effective in many diseases.